Social justice in the EU – Index report 2016. Social Inclusion Monitor Europe - Schraad-Tischler, Daniel; Schiller, Christof (Gütersloh, 2016)
"Based on 36 indicators, the Social Justice Index compares the 28 EU states across six dimensions: Poverty prevention, equitable education, labor market access, social cohesion and non-discrimination, health, as well as intergenerational justice."